(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Solomon’s book Love vs Hope mixes personal accounts with rumination, profiles of the protagonists while has to balance his own passion with the legacy of the New Urbanists, his very personal convictions with a sober reality-bats-last appraisal of the current state of urbanism, with a glum recognition of geopolitical forces, the aspirations of architects.